A randomized clinical trial for the effect of static stretching and strengthening exercise on pelvic tilt angle in LBP patients. Issue 3 (July 2020) - Shamsi, MohammadBagher; Shahsavari, Soodeh; Safari, Ameneh; Mirzaei, Maryam
Abstract: Background: Stretching and strengthening exercises are commonly used to improve muscle shortness of the hamstring as any tension in this muscle can have an effect on the pelvic posture. Thus, the aim of this study was to evaluate the effects of two methods of improving short hamstring on the angle of pelvic tilt in LBP sufferers. Methods: Forty-five low back pain patients aged 19–59 years with hamstring tightness participated in this clinical trial. The patients were categorized randomly into three groups: 1- static stretching, 2-strengthening exercise and 3-control group. The two intervention groups received physical therapy and special exercise program thrice a week in a total of 12 sessions, while the control group received only conventional physical therapy. Before and after the treatment implementation, the pelvic tilt and straight leg raising (SLR) degree were assessed for each group. Result: After 12 sessions of treatment, the ANCOVA models indicated non-significant differences in pelvic tilt angle and SLR score changes (p > 0.05), among the three groups. In addition, no statistically significant correlation was observed between the pelvic tilt and SLR test [except for the strengthening exercise group (Pearson correlation coefficient = −0.54, P < 0.05)]. Conclusions: In LBP sufferers, both static stretching and strengthening of hamstring muscle in its lengthened position caused elongation and extensibility in the hamstring muscle and increased SLR test score, but did not change pelvic tilt angle.